2015
DOI: 10.1186/s13643-015-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of school-based interventions to prevent smoking for girls

Abstract: BackgroundThe purpose of this review is to study the effect of school-based interventions on smoking prevention for girls.MethodsWe performed a systematic review of articles published since 1992 on school-based tobacco-control interventions in controlled trials for smoking prevention among children. We searched the databases of PubMed, Embase, Web of Science, The Cochrane Databases, CINAHL, Social Science Abstracts, and PsycInfo. Two reviewers independently assessed trials for inclusion and quality and extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
0
21
0
2
Order By: Relevance
“…There are “youth to youth” educational and awareness campaigns that can provide education and promote healthy eating. However, these are also strategies than can be targeted by inappropriate marketing and promotion of potentially useless and at times harmful practices . The utilization of mainstream social media for promoting healthy practices and behaviors has special potential for reaching adolescents, especially if the messages can be tailored to promote key practices.…”
Section: Evidence‐based Nutrition Recommendations For Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are “youth to youth” educational and awareness campaigns that can provide education and promote healthy eating. However, these are also strategies than can be targeted by inappropriate marketing and promotion of potentially useless and at times harmful practices . The utilization of mainstream social media for promoting healthy practices and behaviors has special potential for reaching adolescents, especially if the messages can be tailored to promote key practices.…”
Section: Evidence‐based Nutrition Recommendations For Adolescentsmentioning
confidence: 99%
“…However, these are also strategies than can be targeted by inappropriate marketing and promotion of potentially useless and at times harmful practices. [62][63][64] The utilization of mainstream social media for promoting healthy practices and behaviors has special potential for reaching adolescents, especially if the messages can be tailored to promote key practices. These social marketing campaigns use multiple channels and either paid or non-paid content to spread their message widely.…”
Section: Adolescent-friendly Health and Nutrition Services: Integratimentioning
confidence: 99%
“…[5][6][7] School-based interventions have been shown to improve children's health-related attitudes, knowledge and behaviours [8][9][10][11] and enhance children's health literacy through the development of critical thinking and evidence appraisal skills, [12][13] skills which may enable children to make better informed choices about their health. 14 However, despite recent systematic review evidence indicating some positive short term health outcomes associated with school-based interventions [15][16][17] the overall quality of the evidence is mixed, due to methodological limitations 15 and differences in intervention content. 18 The content of school-based programmes tends to focus on strategies for promoting health, with limited consideration of illness and its origins.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional health education interventions, which are often teacher-or expert-led, 18 children were encouraged to discuss health and illness issues that resonated with their own personal experiences and interests, an approach that has been shown to influence children's learning. [35][36] Furthermore, while many health education interventions are delivered as one aspect of the school day, 16 the concept of embedding interventions across the curriculum is not new and studies have shown that such an approach to health education is associated with improved health outcomes. [36][37][38] Furthermore, Facts4Life has potential as a sustainable school-based intervention as its content and activities are explicitly linked to the UK National curriculum, and therefore do not add unduly to time pressures and over-crowding of the school teaching timetable experienced in many schools.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation